Induced Pluripotent Stem Cells Reduce Progression of Experimental Chronic Kidney Disease but Develop Wilms’ Tumors - Heloisa Cristina Caldas; Fernando Henrique Lojudice; Cinthia Dias; Ida Maria Maximina Fernandes-Charpiot; Maria Alice Sperto Ferreira Baptista; Rosa Sayoko Kawasaki-Oyama; Mari Cleide Sogayar; Christina Maeda Takiya; Mario Abbud-Filho (Stem Cells International)
The therapeutic effect of induced pluripotent stem cells (iPSs) on the progression of chronic kidney disease (CKD) has not yet been demonstrated. In this study, we sought to assess whether treatment with iPSs retards progression of CKD when compared with bone marrow mesenchymal stem cells (BMSCs). Untreated 5/6 nephrectomized rats were compared with CKD animals receiving BMSCs or iPSs. Renal function, histology, immunohistochemistry, and gene expression were studied. Implanted iPSs were tracked by the SRY gene expression analysis. Both treatments minimized elevation in serum creatinine, significantly improved clearance, and slowed down progression of disease. The proteinuria was reduced only in the iPS group. Both treatments reduced glomerulosclerosis, iPSs decreased macrophage infiltration, and TGF-β was reduced in kidneys from the BMSC group. Both types of treatments increased VEGF gene expression, TGF-β was upregulated only in the iPS group, and IL-10 had low expression in both groups. The SRY gene was found in 5/8 rats treated with iPSs. These 5 animals presented tumors with histology and cells highly staining positive for PCNA and Wilms’ tumor protein antibody characteristics of Wilms’ tumor. These results suggest that iPSs may be efficient to retard progression of CKD but carry the risk of Wilms’ tumor development.